A Study on Stress Level and Coping Strategies among Undergraduate Students - Y., Ganesan; P., Talwar; Fauzan, Norsiah; Y.B., Oon (Cognition and Interactive Technologies, 2018)
Feelings of stress are a part of university students’ life. Stress is simply the body’s response to changes that create taxing demands. There is a difference between eustress, which is a term for positive stress, and distress, which refers to negative stress. Coping mechanism plays a significant part to overcome or reduce the stress experienced by individuals. People use different types of coping strategies to overcome their stress. The purpose of the study was to study the relationship between stress and coping strategies among university students. Eighty- six university students participated in the study. A quantitative study utilizing a cross sectional non-probability sampling research design was used to gather data. The data was collected using a questionnaire with the addition of Perceived Stress Scale (PSS) and the Adolescent Coping Scale (ACS) were administered. The result of this study indicated that majority of the university students have moderate level of stress. There was a significant inverse relationship between stress level and coping strategies among undergraduates. In conclusion, some levels of stress can be good, as the right kind of stress encourages them towards change and growth. However, when students are unable to cope with stress, they can become a burden. It is recommended that students should be encouraged to take part in extra-curricular activities such as sports to reduce stress. Keywords: Stress; coping strategies; university students